The Science behind Self-regulatory Behaviours of Student Teachers A Neurocognitive Outlook - A. Ananda Kumar; Chellamani, K. (JOURNAL OF INDIAN EDUCATION, 2018)
Teachers play a pivotal role in teaching-learning, societal and nation building. In this perspective, the teacher quality determines students’ learning, societal and national development. The preparation of quality teachers is possible through self-regulation practices in the Teacher Education programme. Self-regulated teachers understand their accountability and the importance of their role. They perform well in preparing lesson plans, curricular designs, teaching aids, word choice, group building and in giving individual attention in teaching and learning. It also facilitates the teachers to sense their students’ mood, body language and classroom environment in their teaching. Neurocognitive concepts explain how the self-regulation process occurs in one’s brain in a scientific way. It also explains how the quality behaviours will emerge. The integration of neurocognitive ideas in the field of education promotes effective performance of teachers as well as the learners. This paper delineates the scientific factors involved in the construction of self-regulated behaviour of student teachers.